Will working students flourish or give up? Exploring the influence of academic psychological capital, grit, and time management - Amadi, W. A.; du Plessis, M.; Solomon, S. (South African Journal of Higher Education, 2022)
Working students are faced with challenges and responsibilities both at university and in their employment. In attempting to study the books and chapters assigned, meet assignment deadlines, participate in extracurricular activities, and functions at work, working students may be overwhelmed. The primary aim of this study was to examine and understand the influence of non-cognitive factors (including Psychological Capital, time management, and grit) on flourishing and the working student’s intention to quit their studies. A non-probability sampling technique indicating convenience sampling and purposive sampling were employed to recruit respondents. The sample (n = 194) was from a residential university in the Western Cape of South Africa. Non-cognitive variables had a positive relationship with flourishing and a negative relationship with intention-to-quit studies. Academic mindset measured as Psychological Capital explained the largest proportion of the variance in flourishing and intention-to-quit studies. Lecturers, counsellors, and university officials should collaborate to incorporate programmes that will aid in developing these non-cognitive variables into the university’s curriculum. These interventions may help improve academic success and throughput of working students.